DOP46 Extended induction treatment with mirikizumab in patients with moderately to severely active ulcerative colitis: results from a Phase 2 trial. (25th January 2019) - Sandborn, W J; Ferrante, M; Bhandari, B R; Berliba, E; Hibi, T; D'Haens, G Geert R; Tuttle, J; Krueger, K; Friedrich, S; Durante, M; Arora, V; Feagan, B
Abstract: Background: Mirikizumab (miri) is a p19-directed IL-23 antibody that has demonstrated clinical efficacy and was well-tolerated following 12 weeks of induction treatment in a Phase 2 trial in patients with ulcerative colitis (UC). 1 Patients without clinical response at Week 12 had access to an open-label (OL) extended induction (EI) for an additional 12 weeks. Week-24 extended-induction results (12 weeks induction plus 12 weeks extended induction) are reported. Methods: Patients with moderately to severely active UC (Mayo score 6–12 with a minimum endoscopic subscore [ES] ≥2) were randomised 1:1:1:1 to receive intravenous (IV) placebo (pbo, N = 63), miri 50 mg ( N = 63) or 200 mg ( N = 62) with possibility of exposure-based (EB) dose increases, or miri 600 mg ( N = 61) every 4 weeks (Q4W), with efficacy assessment at Week 12. Non-responders (NR; see Table 1 for definition) at Week 12 had access to OL miri: extended induction for an additional 12 weeks for patients who had received induction miri (miri NR) and 12 weeks miri for patients who had received induction pbo (pbo NR). The first group of patients to enter the EI arm received OL miri 600 mg IV Q4W ( N = 20). After a protocol amendment, subsequent patients entering the EI arm received OL miri 1000 mg IV Q4W ( N = 64). Safety and clinical outcome (see Table 1 for definitions) data were collected throughout EI, with primary clinical activity assessment at Week 24 of study. Results: Among miri NR, 50.0% and 43.8% receiving 12 weeks of 600 mg or 1000 mg miri, respectively, achieved clinical response, 15.0% and 9.4% achieved clinical remission, 20.0% and 15.6% had ES = 0/1, and 0 and 3.0% had an ES = 0 at the end of the EI (Week 24). Among pbo NR, 58.0% and 71.9% receiving 12 weeks of 600 mg or 1000 mg miri, respectively, achieved clinical response, 25.0% and 25.0% achieved clinical remission, 25.0% and 37.5% had ES = 0/1, and 0 and 9.4% had an ES = 0 at the end of the EI (Week 24). Treatment-emergent adverse events (AEs), discontinuations due to AE, and serious AEs were similar across treatment groups during the EI. Conclusions: An additional 12 weeks of induction treatment allowed 43.8–50.0% of induction miri NR to achieve clinical response. Patients treated with 600 mg or 1000 mg miri Q4W had few serious AEs and discontinuations due to AEs. No new safety concerns were identified during 24 weeks of induction treatment with miri.